EFEKTIVITAS DAN EFISIENSI PELAKSANAAN MANAJEMEN BERBASIS KOMPOTENSI DALAM MENCAPAI TUJUAN SEKOLAH - Lubis, Rosimah (AIN Padangsidimpuan, 2014)
AbstrackThis MBC is to increase efficiency quality and distribution of education. The improving efficiency is obtained through facility to manage existing resource, society participation and to moderate bureaucracy. Improvement of quality is obtained through old fellow participation, flexing management of school, improving teachers’ professionalism, existence of penalization and present as control are able to grow development of conducive atmosphere. Generalization of visible education at growing society participation especially is capable and care, whereas the indigent will become governmental responsibility.Keywords: Affectivity, Efficiency Management and Competence